Preparation method of PVC plasticized paste

Through the composite modification of calcium carbonate, the lubrication and dispersion effects of ether chains and alkyl chains are used to solve the problem of agglomeration of calcium carbonate in PVC plasticizing paste, achieving uniform dispersion and stability improvement, and improving mechanical properties and Productivity.

CN119264580AActive Publication Date: 2025-01-07JINING ZHONGYIN ELECTRO-CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411580217.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The agglomeration of calcium carbonate in PVC plasticizing paste leads to poor dispersion, affecting mechanical properties and processing properties, and the stability of existing surface treatment methods is insufficient, affecting storage stability.

Method used

The calcium carbonate is modified by silane coupling agent, polyethylene glycol meth ether acrylate and octadecene are introduced, and the compatibility and fluidity of calcium carbonate are improved through the lubrication and dispersion effects of ether chains and alkyl chains. It also works in concert with the plasticizer to form composite modified calcium carbonate, which is used for the preparation of PVC plasticizing paste.

Benefits of technology

The uniform dispersion of calcium carbonate in PVC plasticizing paste is achieved, the system viscosity and scratch particle size are reduced, storage stability and mechanical properties are improved, and processing performance and production efficiency are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122860890000081
    Figure BDA0005122860890000081
Patent Text Reader

Abstract

The invention relates to the technical field of polyvinyl chloride, in particular to a preparation method of PVC plasticized paste. The preparation method comprises the following steps: mixing 5-20 parts by weight of PVC paste resin, 3-15 parts by weight of composite modified calcium carbonate and 1-5 parts by weight of a plasticizer, and stirring at a speed of 800-1200 rpm for 15-30 min to obtain PVC plasticized paste; polyethylene glycol methyl ether acrylate and octadecene are used as composite modifiers, and are grafted to the surface of vinyl silane modified calcium carbonate through polymerization reaction to obtain the composite modified calcium carbonate. The PVC plastifying paste prepared by the invention has the characteristic of stable low viscosity, and the product of the PVC plastifying paste has higher mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl chloride, in particular to a preparation method of PVC plastisol. Background Art

[0002] In the plastics industry, polyvinyl chloride (PVC) is widely used in the fields of construction, automobile, medical treatment, etc. due to its excellent physical and chemical properties, easy processing and cost-effectiveness. In particular, PVC plastisol has become an ideal material for the production of coating, dipping, spraying and molding products due to its unique rheological properties and processing adaptability.

[0003] Calcium carbonate is a commonly used inorganic filler in PVC plasticizer paste to improve mechanical properties, reduce costs, and improve thermal stability. However, calcium carbonate particles often agglomerate in the matrix, resulting in poor dispersibility, which in turn impairs the mechanical properties and processing properties of the polymer system. Therefore, how to solve the agglomeration problem of calcium carbonate in the matrix while improving the performance of PVC paste resin is a difficult problem that material scientists need to solve urgently.

[0004] Patent technology document CN201510946405.9 discloses a surface treatment method for nano calcium carbonate filled with PVC plastisol, using a composite mixture of saturated fatty acid and sodium ricinoleate sulfate to treat the surface of nano calcium carbonate, and the treated nano calcium carbonate can effectively improve the thixotropy, yield value and rheological stability of the filled PVC plastisol. However, saturated fatty acid and sodium ricinoleate sulfate are physically adsorbed on the surface of calcium carbonate and are easily detached, thereby affecting the storage stability of PVC plastisol. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for preparing a PVC plastisol to solve the problem that the calcium carbonate in the calcium carbonate-filled modified PVC plastisol has poor stability and serious agglomeration over time, thereby resulting in poor storage stability of the PVC plastisol.

[0006] Based on the above purpose, the present invention provides a method for preparing PVC plastisol, which comprises mixing 5-20 parts of PVC paste resin, 3-15 parts of composite modified calcium carbonate and 1-5 parts of plasticizer by weight, and stirring at a speed of 800-1200 rpm for 15-30 minutes to obtain PVC plastisol.

[0007] Preferably, the PVC paste resin is prepared by a seed emulsion method and has a degree of polymerization of 1500-2100.

[0008] Preferably, the plasticizer is one of dioctyl phthalate and tri-n-butyl acetyl citrate or a mixture of both.

[0009] More preferably, the plasticizer is a mixture of dioctyl phthalate and tri-n-butyl acetyl citrate in a weight ratio of 3:1.

[0010] Furthermore, the preparation method of the composite modified calcium carbonate is as follows:

[0011] (1) Using silane coupling agent KH-570 to graft calcium carbonate to obtain vinyl silane modified calcium carbonate;

[0012] (2) Polyethylene glycol methyl ether acrylate and octadecene are used as composite modifiers and grafted onto the surface of vinyl silane-modified calcium carbonate through polymerization reaction to obtain composite modified calcium carbonate.

[0013] Preferably, the amount of silane coupling agent used in step (1) is 1%-5% by weight of calcium carbonate.

[0014] Preferably, the average particle size of calcium carbonate in step (1) is 80-100 nm.

[0015] Preferably, the specific preparation steps of the vinyl silane-modified calcium carbonate in step (1) are as follows: adding calcium carbonate to a mixture of deionized water and anhydrous ethanol, ultrasonically dispersing for 5-20 minutes, then adding silane coupling agent KH-570, heating to 40-50° C., stirring for 8-15 hours, and after the reaction is completed, washing and drying to obtain vinyl silane-modified calcium carbonate.

[0016] Preferably, in step (2), the weight ratio of the composite modifier to the vinylsilane-modified calcium carbonate is 2-5:1;

[0017] Preferably, in step (2), the molar ratio of polyethylene glycol methyl ether acrylate to octadecene is 1:2-8.

[0018] Preferably, the weight average molecular weight of the polyethylene glycol methyl ether acrylate in step (2) is 400-500.

[0019] Preferably, the initiator used in the polymerization reaction in step (2) is azobisisobutyronitrile.

[0020] Preferably, the polymerization reaction temperature in step (2) is 55-65° C. and the reaction time is 20-30 h.

[0021] Beneficial effects of the present invention:

[0022] The present invention achieves uniform dispersion of calcium carbonate in PVC plastisol by composite modification, showing good compatibility. This characteristic effectively reduces the system viscosity and scratch particle size of the plastisol, avoids problems such as sticking to the roller during the production process, and thus improves production efficiency. At the same time, it has stable low viscosity characteristics, excellent storage stability, and is easy to transport and store for a long time.

[0023] The present invention introduces polyethylene glycol methyl ether acrylate on the surface of calcium carbonate, and through the lubricating effect of its ether chain, not only the viscosity of the system is reduced, but also the good fluidity and dispersibility of calcium carbonate are promoted, especially under the synergistic effect with the plasticizer, the flexibility and mobility of the polymer chain are increased, the interchain entanglement is reduced, and the processing performance of the material is further improved.

[0024] The present invention further introduces octadecene on the surface of calcium carbonate, and its unique long-chain alkyl effect reduces the agglomeration of calcium carbonate in PVC plasticizer paste, which not only reduces the viscosity of the system but also improves the mechanical properties of its products.

[0025] The composite modification of calcium carbonate in the present invention shows a synergistic effect in improving the tensile strength and elongation at break of PVC plastic paste products, especially the significant improvement of elongation at break by ether chains, which is attributed to the reinforcing effect of calcium carbonate and the toughening effect of its surface alkyl chains and ether chains.

[0026] The invention further accurately controls the mechanical properties of the PVC plasticized paste product by optimizing the dosage of polyethylene glycol methyl ether acrylate and octadecene. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0028] The weight average molecular weight of the polyethylene glycol methyl ether acrylate used in the examples and comparative examples of the present invention is 480; the PVC paste resin is prepared by a seed emulsion method, and the degree of polymerization is 1500-2100; the calcium carbonate is cubic in shape, and the average particle size is 90 nm.

[0029] Example 1: (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 10 min. Then, 0.15 g of silane coupling agent KH-570 was added, the temperature was raised to 45° C., and stirred for 12 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate.

[0030] (2) 4.6 g of polyethylene glycol methyl ether acrylate and 10 g of octadecene were added to anhydrous ethanol, stirred for 30 min, and then 5 g of vinyl silane-modified calcium carbonate was added, ultrasonicated for 20 min, and then 0.15 g of azobisisobutyronitrile was added, the temperature was raised to 60° C., stirred for 24 h, centrifuged, washed with anhydrous ethanol for 3 times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0031] (3) 10 g of PVC paste resin, 7.5 g of composite modified calcium carbonate and 2 g of dioctyl phthalate were mixed and stirred at a speed of 1000 rpm for 20 min to obtain a PVC plasticized paste.

[0032] Example 2: (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 5 min. Then, 0.05 g of silane coupling agent KH-570 was added, the temperature was raised to 40° C., and stirred for 8 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate.

[0033] (2) 5 g of polyethylene glycol methyl ether acrylate and 5 g of octadecene were added to anhydrous ethanol, stirred for 20 min, and then 5 g of vinyl silane-modified calcium carbonate was added, ultrasonicated for 15 min, and then 0.1 g of azobisisobutyronitrile was added, the temperature was raised to 55° C., stirred for 20 h, centrifuged, washed with anhydrous ethanol for 3 times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0034] (3) 5 g of PVC paste resin, 3 g of composite modified calcium carbonate and 1 g of dioctyl phthalate were mixed and stirred at 800 rpm for 15 min to obtain a PVC plasticized paste.

[0035] Example 3: (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 20 min. Then, 0.25 g of silane coupling agent KH-570 was added, the temperature was raised to 50° C., and stirred for 15 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate.

[0036] (2) 5 g of polyethylene glycol methyl ether acrylate and 20 g of octadecene were added to anhydrous ethanol, stirred for 40 min, and then 5 g of vinyl silane-modified calcium carbonate was added, ultrasonicated for 30 min, and then 0.25 g of azobisisobutyronitrile was added, the temperature was raised to 65° C., stirred for 30 h, centrifuged, washed with anhydrous ethanol for 3 times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0037] (3) 20 g of PVC paste resin, 15 g of composite modified calcium carbonate and 5 g of dioctyl phthalate were mixed and stirred at 1200 rpm for 30 min to obtain PVC plasticized paste.

[0038] Example 4: (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 10 min. Then, 0.15 g of silane coupling agent KH-570 was added, the temperature was raised to 45° C., and stirred for 12 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate.

[0039] (2) 4.6 g of polyethylene glycol methyl ether acrylate and 10 g of octadecene were added to anhydrous ethanol, stirred for 30 min, and then 5 g of vinyl silane-modified calcium carbonate was added, ultrasonicated for 20 min, and then azobisisobutyronitrile was added, the temperature was raised to 60° C., stirred for 24 h, centrifuged, washed with anhydrous ethanol for 3 times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0040] (3) 10 g of PVC paste resin, 7.5 g of composite modified calcium carbonate, 1.5 g of dioctyl phthalate and 0.5 g of tri-n-butyl acetyl citrate were mixed and stirred at 1000 rpm for 20 min to obtain a PVC plasticized paste.

[0041] Comparative Example 1:

[0042] The difference between Comparative Example 1 and Example 1 is that the composite modified calcium carbonate in step (3) is replaced by vinylsilane modified calcium carbonate;

[0043] The specific preparation steps are as follows:

[0044] (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 10 min. Then, 0.15 g of silane coupling agent KH-570 was added, and the mixture was heated to 45° C. and stirred for 12 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate;

[0045] (2) 10 g of PVC paste resin, 7.5 g of vinyl silane-modified calcium carbonate and 2 g of dioctyl phthalate were mixed and stirred at 1000 rpm for 20 min to obtain a PVC plasticized paste.

[0046] Comparative Example 2:

[0047] The difference between Comparative Example 2 and Example 1 is that: polyethylene glycol methyl ether acrylate is not added in step (2);

[0048] The specific preparation steps are as follows:

[0049] (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 10 min. Then, 0.15 g of silane coupling agent KH-570 was added, and the mixture was heated to 45° C. and stirred for 12 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate;

[0050] (2) 14.6 g of octadecene was added to anhydrous ethanol, stirred for 30 min, and then 5 g of vinylsilane-modified calcium carbonate was added, ultrasonicated for 20 min, and then 0.15 g of azobisisobutyronitrile was added, the temperature was raised to 60° C., stirred for 24 h, centrifuged, washed with anhydrous ethanol three times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0051] (3) 10 g of PVC paste resin, 7.5 g of composite modified calcium carbonate and 2 g of dioctyl phthalate were mixed and stirred at a speed of 1000 rpm for 20 min to obtain a PVC plasticized paste.

[0052] Comparative Example 3:

[0053] The difference between Comparative Example 3 and Example 1 is that: octadecene is not added in step (2);

[0054] The specific steps are as follows:

[0055] (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 10 min. Then, 0.15 g of silane coupling agent KH-570 was added, and the mixture was heated to 45° C. and stirred for 12 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate;

[0056] (2) 14.6 g of polyethylene glycol methyl ether acrylate was added to anhydrous ethanol, stirred for 30 min, and then 5 g of vinyl silane-modified calcium carbonate was added, ultrasonicated for 20 min, and then 0.15 g of azobisisobutyronitrile was added, the temperature was raised to 60° C., stirred for 24 h, centrifuged, washed with anhydrous ethanol for 3 times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0057] (3) 10 g of PVC paste resin, 7.5 g of composite modified calcium carbonate and 2 g of dioctyl phthalate were mixed and stirred at a speed of 1000 rpm for 20 min to obtain a PVC plasticized paste.

[0058] Comparative Example 4:

[0059] The difference between Comparative Example 4 and Example 1 is that the molar ratio of polyethylene glycol methyl ether acrylate to octadecene in step (2) is 4:1.

[0060] The specific steps are as follows:

[0061] (1) 5 g of calcium carbonate was added to a mixture of 10 g of deionized water and 90 g of anhydrous ethanol, and ultrasonically dispersed for 10 min. Then, 0.15 g of silane coupling agent KH-570 was added, and the mixture was heated to 45° C. and stirred for 12 h. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 60° C. for 24 h to obtain vinyl silane-modified calcium carbonate;

[0062] (2) 18.4 g of polyethylene glycol methyl ether acrylate and 2.5 g of octadecene were added to anhydrous ethanol, stirred for 30 min, and then 5 g of vinyl silane-modified calcium carbonate was added, ultrasonicated for 20 min, and then 0.15 g of azobisisobutyronitrile was added, the temperature was raised to 60° C., stirred for 24 h, centrifuged, washed with anhydrous ethanol for 3 times, and dried at 60° C. for 12 h to obtain a composite modified calcium carbonate;

[0063] (3) 10 g of PVC paste resin, 7.5 g of composite modified calcium carbonate and 2 g of dioctyl phthalate were mixed and stirred at a speed of 1000 rpm for 20 min to obtain a PVC plasticized paste.

[0064] Performance Test:

[0065] The viscosity and scratch particle size of the PVC plastisol prepared in the examples and comparative examples were tested. The results are shown in Table 1. PVC test pieces were prepared according to the standard baking method and the tensile strength and elongation were tested. The results are shown in Table 2.

[0066] Table 1 Test results of viscosity and scratch particle size

[0067]

[0068] Data Analysis:

[0069] It can be seen from the data of Examples 1-4 in Table 1 that the PVC plastisol provided by the present invention has a lower viscosity and a smaller scratch particle size, indicating that the composite modified calcium carbonate is uniformly dispersed in the PVC plastisol and has excellent compatibility with the PVC plastisol. The appropriate viscosity helps to avoid the phenomenon of sticking to the roller during the production process on the machine, thereby improving the production efficiency. In addition, the PVC plastisol prepared by the present invention has a stable viscosity within 0-12 hours, indicating that it has excellent stability and is easy to store.

[0070] It can be seen from Example 1 and Comparative Example 1 in Table 1 that the composite modification of calcium carbonate helps to reduce the system viscosity and scratch particle size of the PVC plastisol and improve the stability. The improvement in stability may be due to the lubricating effect of polyethylene glycol methyl ether acrylate and the synergistic dispersing effect of octadecene.

[0071] It can be seen from Example 1 and Comparative Example 2 in Table 1 that the use of polyethylene glycol methyl ether acrylate can effectively reduce the system viscosity of the PVC plastisol. This is mainly because the ether chain of polyethylene glycol methyl ether acrylate helps to promote the flow of calcium carbonate in the system, and synergistically increases the flexibility of the polymer chain and the mobility of the chain segments with the plasticizer, reducing the entanglement between the polymer chains.

[0072] It can be seen from Example 1 and Comparative Example 3 in Table 1 that the use of octadecene can effectively reduce the system viscosity of the PVC plastisol, which is mainly because the long alkyl chain of octadecene can reduce the agglomeration of calcium carbonate in the PVC plastisol.

[0073] It can be seen from Example 1 and Comparative Example 4 in Table 1 that the dosage of polyethylene glycol methyl ether acrylate and octadecene has a significant effect on the stability of the PVC plastisol.

[0074] Table 2 Mechanical properties of PVC test pieces

[0075] PVC test piece Tensile strength / MPa Elongation at break / % Example 1 18.4 482 Example 2 17.2 512 Example 3 17.8 495 Example 4 19.3 489 Comparative Example 1 17.3 463 Comparative Example 2 19.2 454 Comparative Example 3 16.7 498 Comparative Example 4 16.9 491

[0076] Data Analysis:

[0077] It can be seen from the data of Examples 1-4 in Table 2 that the PVC test pieces prepared from the PVC plastisol provided by the present invention have excellent mechanical properties.

[0078] It can be seen from the data of Example 1 and Comparative Examples 1-3 in Table 2 that the composite modification of calcium carbonate helps to simultaneously improve the tensile strength and elongation at break of the PVC test piece, among which the ether chain has the most significant effect on the elongation at break of the PVC test piece, which may be due to the reinforcing effect of calcium carbonate itself and the toughening effect of the alkyl chain and ether chain on the surface of calcium carbonate.

[0079] It can be seen from the data of Example 1 and Comparative Example 4 in Table 2 that the dosage of polyethylene glycol methyl ether acrylate and octadecene is crucial to adjusting the tensile strength and elongation at break of the PVC test piece. Excessive dosage of polyethylene glycol methyl ether acrylate will greatly reduce the tensile strength of the PVC test piece.

[0080] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing PVC plastisol, characterized in that: Mix 5-20 parts of PVC paste resin, 3-15 parts of composite modified calcium carbonate and 1-5 parts of plasticizer by weight, and stir at a speed of 800-1200 rpm for 15-30 minutes to obtain PVC plasticized paste; The preparation method of the composite modified calcium carbonate is as follows: (1) Using silane coupling agent KH-570 to graft calcium carbonate to obtain vinyl silane modified calcium carbonate; (2) using polyethylene glycol methyl ether acrylate and octadecene as composite modifiers, grafting them onto the surface of vinyl silane-modified calcium carbonate through polymerization reaction to obtain composite modified calcium carbonate; The amount of the silane coupling agent used in step (1) is 1%-5% of the weight of calcium carbonate; In the step (2), the weight ratio of the composite modifier to the vinylsilane-modified calcium carbonate is 2-5:1; In the step (2), the molar ratio of polyethylene glycol methyl ether acrylate to octadecene is 1:2-8.

2. The method for preparing PVC plastisol according to claim 1, characterized in that: The PVC paste resin is prepared by a seed emulsion method and has a polymerization degree of 1500-2100.

3. The method for preparing PVC plastisol according to claim 1, characterized in that: The plasticizer is one of dioctyl phthalate and tri-n-butyl acetyl citrate or a mixture of the two.

4. The method for preparing PVC plastisol according to claim 3, characterized in that: The plasticizer is a mixture of dioctyl phthalate and tri-n-butyl acetyl citrate in a weight ratio of 3:

1.

5. The method for preparing PVC plastisol according to claim 1, characterized in that: The average particle size of calcium carbonate in step (1) is 80-100 nm.

6. The method for preparing PVC plastisol according to claim 1, characterized in that: The specific preparation steps of the vinyl silane-modified calcium carbonate in step (1) are as follows: adding calcium carbonate to a mixture of deionized water and anhydrous ethanol, ultrasonically dispersing for 5-20 minutes, then adding silane coupling agent KH-570, heating to 40-50° C., stirring for 8-15 hours, and after the reaction is completed, washing and drying to obtain vinyl silane-modified calcium carbonate.

7. The method for preparing PVC plastisol according to claim 1, characterized in that: The weight average molecular weight of the polyethylene glycol methyl ether acrylate in the step (2) is 400-500.

8. The method for preparing PVC plastisol according to claim 1, characterized in that: The initiator used in the polymerization reaction in step (2) is azobisisobutyronitrile.

9. The method for preparing PVC plastisol according to claim 1, characterized in that: The polymerization reaction temperature in step (2) is 55-65° C. and the reaction time is 20-30 hours.

Citation Information

Patent Citations

  • A kind of surface treatment method of nano-calcium carbonate filled with pvc plastisol

    CN105400238B